'But I'm not a doctor': pending trust in science among laypeople discussing the brain disease model of addiction. (4th July 2019) - Bogren, Alexandra
Abstract: Aim: In recent decades, the notion of addiction as a brain disease has become influential among scientists, public institutions, and addiction treatment professionals, and its popularity raises the question of how biomedical science affects public perceptions of illness. Although existing research has examined how laypeople interpret disease models of addiction, few studies address how they interpret the brain disease model as presented by the media, the version that most citizens are likely to encounter in their everyday lives. This article contributes to existing research by examining Swedish laypeople's interpretations of a news article presenting biomedical research on addiction and analyzing how trust intervenes in their interpretations. Methods: Drawing on an audience study design with qualitative interviews, the participants were asked to read and discuss a newspaper article that explained how alcohol, amphetamine, and nicotine affect the brain. Results: The analysis shows that their interpretations depended on how they perceived their own ability to assess the science portrayed in the article. The participants trust doctors and scientists but doubt their own ability to assess the science, and trust is therefore provisional or pending until this situation changes. In addition, trust requires that the participants are able to recognize and identify with the contents of the news article. Conclusion: This pattern can be understood as a way of dealing with the contradictory expectations laypeople face – they are expected to trust scientific knowledge and to evaluate knowledge claims rationally, but they do not have access to the knowledge that would, supposedly, enable them to do so.